EMOTIONAL INDOCTRINATION DISGUISED AS EMPOWERMENT: THE IMPACT OF DIGITAL SMUT ON YOUTH (Contemporary Journal of Social Science Review, 2025)
This study examines how digital erotic literature and hypersexual content on platforms like Wattpad, TikTok, and OnlyFans influence adolescents and young adults aged 15–22. It argues that smut works as emotional indoctrination disguised as empowerment, reshaping how youth perceive love, intimacy, and identity. Through a literature review and a survey of 103 participants, we find that exposure normalises unhealthy relationships, causes desensitisation, and encourages addiction-like behaviour. In the survey 75.7% of people said they engaged with online smut regularly, most encountering it passively. Over half of the responses reported emotional numbness afterwards, and many described real-life intimacy as underwhelming in comparison. Meanwhile, 73% acknowledged that smut shaped their perception of love. This shows recurring themes including the romanticisation of pain, and how intensity outweighs intimacy. We conclude by discussing the role of algorithms, historical parallels, and ethical concerns. The findings highlight the urgency for media literacy and safeguards that address explicitness and the emotional logic in youth-oriented smut.